Some Parasites From Gills of Five Fish Species and the First Record of the Monogenean Ligophorus Imitans Euzet et Suriano, 1977 in Iraq - Al-Saadi, Abd Ali J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Five fish species were collected from Tigris river at Al-Adhamiyah region, Baghdad during the period from September to December 2011. These fishes were examined for ectoparasites. They were infected with 13 species of parasites which included one species of ciliated protozoans and 12 species of monogeneans. Among such parasites, Ligophorus imitans Euzet et Suriano, 1977 is reported for the first time in Iraq. In addition, eight new host records in Iraq were reported in the present study.